INNOVATIONS IN TEACHING GENERAL PEDAGOGICAL SCIENCE - Muratova Shaxnoza Ibatovna (American Journals, 2023)
In this article, social sciences, the development of specialists in the process of globalization, additional research in the pedagogical process, innovative technologies, educational innovations, several types of educational innovations, the innovative activity of a teacher, his professional and personal characteristics, the professional development of his thinking, formation of skills and qualifications.
Keywords: Innovation, educational innovations, innovation, activity, innovative activity, graphic organizer, pedagogical technologies.